Exploring pain management preferences: a discrete choice experiment on cannabis or opioids among middle-aged and older adults - Rudiel Fabian; Paul Brown; Ricardo Cisneros (Journal of Health, Population and Nutrition)
Abstract Objective The study examines middle-aged and older adult’s preferences to identify policies that might increase the use of cannabis rather than opioids for controlling physical pain. Method A discrete choice survey was administered to 301 older adults (≥ 40 years) in three California regions (Los Angeles, Bay Area, and San Joaquin Valley). Participants expressed preferences for pain medication under mild, moderate, and severe pain scenarios. Each participant made 16 choices between options that varied by medication type (medical cannabis, opioids, over-the-counter medications, or none), effectiveness, accessibility, side effects, addictiveness, and cost of the medication. A conditional logit model (CLM) was used to analyze the results for the entire sample, stratified by pain levels, and according to whether the participant had previous experience with taking medications for physical pain. Results The results suggest that, all else equal, over-the-counter (OTC) treatments were the most preferred option for pain management. However, individuals were also willing to consider cannabis as a secondary treatment. Respondents with previous cannabis experience, either medically or recreationally, were more likely to select cannabis as their primary treatment choice. Marginal analysis revealed that the policy option of doubling opioid costs led to the greatest reduction in opioid use and increased the likelihood of cannabis use. Conclusions Cannabis is a viable alternative to opioids for controlling pain. Findings suggest that interest in cannabis relative to opioids is high, and that messages that emphasize the addictiveness of opioids relative to cannabis might be particularly effective in decreasing opioid use.